Crime Organized Transnational: Characteristics Terrorism and Threats Terrorism via Social Media - Ali Ramadan; Laksanto Utomo; Edi Saputra Hasibuan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Advances in information technology are changing the propaganda patterns of terrorist groups from conventional methods to more modern methods by using cyberspace as a new means of carrying out acts of terrorism or often called cyberterrorism. Using normative legal research with a qualitative research approach, the author conducted research with the aim of discussing in more depth the reasons why terrorism is included in transnational crime and the characteristics of terrorism in cyberspace. literature study method with a legal approach and other secondary legal materials in order to obtain satisfactory results. The results of this research show that transnational organized crime includes many things, one of which is terrorism. The crime of terrorism in its most typical form is a combination of crime and the need to have work appropriate to the main crime or specific goals for terrorism itself. This is what causes the crime of terrorism to be included in transnational crimes because it can cover both national and international scope. Apart from that, there are at least 5 characteristics contained in this research which show that this crime is part of cyber crime and terrorism is also part of international crime.